Fault-tree-based instantaneous risk computing core in nuclear power plant risk monitor. (September 2016) - Wang, Jin; Wang, Fang; Chen, Shanqi; Wang, Jiaqun; Hu, Liqin; Yin, Yuan; Wu, Yican
Highlights: A fast fault-tree-based instantaneous risk computing core in NPP risk monitor. A set of algorithms based on the Zero-suppressed Binary Decision Diagram. Benchmarks of actual nuclear power plant (NPP) instantaneous risk models. Applications in risk monitor for Third Qinshan Nuclear Power Plants in China. Abstract: Risk monitor is an application of Probabilistic Safety Assessment (PSA) methodology, which has been widely used to determine the instantaneous risk based on the actual configuration of the nuclear power plant (NPP). The instantaneous risk model which has been converted from the baseline risk model of PSA is the fundament of instantaneous risk analysis in a risk monitor. However, the instantaneous risk model is usually very huge and complex, which is hard to be calculated and analyzed by hand. A fault-tree-based instantaneous risk computing core was developed by FDS Team. This code adopts the fast fault tree analysis method based on modified Zero-suppressed Binary Decision Diagram (ZBDD), which includes a set of algorithms such as fault tree importing, fault tree reduction, ZBDD variable ordering, ZBDD parallel manipulation and cut-sets-based ZBDD reconstruction, etc. Benchmarks of actual NPP instantaneous risk models compared with similar codes showed that this code was correct and efficient. This computing core was applied in the Third Qinshan NPP risk monitor TQRM, and some cases based on the actual NPP instantaneous risk models are given.